A Bio-Inspired Approach to Improve the Toughness of Brittle Bast Fibre-Reinforced Composites Using Cellulose Acetate Foils - Nina Graupner; Jörg Müssig (Biomimetics, 2024)
Bast fibre-reinforced plastics are characterised by good strength and stiffness but are often brittle due to the stiff and less ductile fibres. This study uses a biomimetic approach to improve impact strength. Based on the structure of the spicules of a deep-sea glass sponge, in which hard layers of bioglass alternate with soft layers of proteins, the toughness of kenaf/epoxy composites was significantly improved by a multilayer structure of kenaf and cellulose acetate (CA) foils as impact modifiers. Due to the alternating structure, cracks are deflected, and toughness is improved. One to five CA foils were stacked with kenaf layers and processed to composite plates with bio-based epoxy resin by compression moulding. Results have shown a significant improvement in toughness using CA foils due to increased crack propagation. The unnotched Charpy impact strength increased from 9.0 kJ/m2 of the pure kenaf/epoxy composite to 36.3 kJ/m2 for the sample containing five CA foils. The tensile and flexural strength ranged from 74 to 81 MPa and 112 to 125 MPa, respectively. The tensile modulus reached values between 9100 and 10,600 MPa, and the flexural modulus ranged between 7200 and 8100 MPa. The results demonstrate the successful implementation of an abstract transfer of biological role models to improve the toughness of brittle bast fibre-reinforced plastics.